Control and prevention of streptococcosis in cultured tilapia in Malaysia: a review - Saad, Mohd Zamri; Azmai, Mohammad Noor Amal; Abdullah, Siti Zahrah; Abd. Rashid, Zulkafli (Universiti Putra Malaysia Press, 2014)
Streptococcosis in cultured fishes has been reported to cause severe economic losses to the aquaculture industry worldwide. Lancefield group B Streptococcus agalactiae has been recognised as the main pathogen in cultured tilapia. This review discusses the current scenario and risk factors of streptococcosis in tilapia and suggests the control and prevention measures for this disease. The preventive measures focus on combined aspects of selecting farm location, applying good aquaculture farm practices, utilization of antibiotics and proper vaccination programme. A combination of all these measures will perhaps be the key to improve the health of cultured tilapia and prevent the infection by S. agalactiae, which in turn will increase the economic profit of tilapia farm operators.